KAJIAN PENGGUNAAN SOFTWARE ZAHIR ACCOUNTING DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (Studi Kasus : Mahasiswa Program Studi Komputerisasi Akuntansi AMIK “BSI Bogor”) - Kudiantoro Widianto (Universitas Bina Sarana Informatika, 2015)
Zahir Accounting Software use this caused a reaction on its self, in the form of acceptance or rejection. Due to the success of the application of information technology is subject to acceptance by the user as the user of technology. A technology acceptance model known as TAM (Technology Acceptance Model) can explain and predict the acceptance of the technology by the user. TAM models used to determine attitudes, intentions and behavior of users by using two main input variables of expediency and convenience. This study by spreading the questionnaire number 117 in the form of a closed question in the form of statements to know how to influence the perception of self-efficacy variable of Computer Self Efficacy (CSE), Perceived Ease of Use (PEoU), Perceived usefulness (PU), the Attitude Toward using (ATU), Behavioral Intention to Use (BITU) and Actual System Usage (ASU). Factors that affect the acceptance of the use of Software Zahir in Bogor BSI AMIK Computerized Accountancy Studies on research studies Zahir Accounting Software usage capabilities include themselves on the computer, perceived ease of use, perceived usefulness, the attitude to use, behavioral intention to use and actual use system.Keywords: Zahir Accounting, TAM, SEM, dan AMOS